THE INFLUENCE OF EMPOWERMENT, BELIEF, AND REWARD TOWARD EMPLOYEE’S COMMITMENT AT MOTHER AND CHILD HOSPITAL OF ERIA BUNDA PEKANBARU - Rofidah, Siti (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
The purposes of this research were to know the influence of empowerment, belief, and reward simultaneously and partially and to know which one the highest aspect influence employee’s commitment at mother and child hospital of Eria Bunda Pekanbaru. The method of this research used quantitative research and designed with correlational research. The population in this research was 164 employees. By using random sampling method, it can be calculated that the sample was 116 respondents. Then, the data collection technic used questionnaire and interview. In finding the quantity of an independent variable, influence with dependent variable used multiple linear regression analysis. This research concluded that empowerment, belief, and reward simultaneously gave significant influence toward employee’s commitment. Partially, empowerment had significant influence, which was dominated toward employee’s commitment. Meanwhile, belief and reward did not have influence toward employee’s commitment